HAJI MUHYIDDINZAIN: tokoh Pendidikan tinggi Islam di sulawesi selatan - Hamdar Arraiyyah (Badan Litbang dan Diklat Kementerian Agama RI, 2016)
abstractThis paper describes a character that lived in the twentieth century and was instrumental in developing Islamic higher education in South Sulawesi. The role of this figure is not known by the recent generations because it is not much publicized. The struggle of the figure is shown by, among other things, his achievement as the first man in this area who earned a degree in religious college and his role as the founder and head of an Islamic higher educational institution. Data and information on the figure obtained through written sources and interviews with people who’ve hung out with him like his close relatives, fellow professors at university, friends in the organization and direct observations of the author of a number of activities during his lifetime. The information based on those sources is combined into a brief biography as part of a study of history. An explanation of the figure refers to the standpoint of leadership theory, particularly the nature and personality of a leader as well as his effective leadership.Keywords: Leaders, educators, Islamic Universities educational abstraktulisan ini menjelaskan seorang tokoh yang hidup pada abad dua puluh dan banyak berjasa dalam mengembangkan pendidikan tinggi Islam di sulawesi selatan. Peran tokoh ini belum banyak dikenal oleh generasi sesudahnya karena belum banyak dipublikasikan. Perjuangan tokoh dijelaskan, antara lain, dengan capaian sebagai orang pertama di daerah ini yang meraih gelar sarjana di perguruan tinggi agama, mendirikan dan memimpin lembaga pendidikan tinggi Islam. Data dan informasi tentang tokoh diperoleh melalui sumber tertulis dan wawancara dengan orang-orang yang pernah bergaul dengannya seperti kerabat dekat, sesama dosen di kampus, sahabat dalam organisasi dan pengamatan langsung penulis terhadap sejumlah aktivitas tokoh semasa hidupnya. Informasi berdasarkan sumber-sumber itu dipadukan menjadi suatu biografi singkat sebagai bagian dari kajian sejarah. Penjelasan tentang ketokohan mengacu pada sudut pandang teori kepemimpinan, khususunya sifat dan kepribadian seorang pemimpin serta kepemimpinan efektif.Kata Kunci: tokoh, Pendidik, Perguruan tinggi Islam